Quality Status of Coastal Waters of Special Economic Zone of Mandalika Central Lombok Based on the Community of Microalgae as Bioindicator - Lalu Japa; Karnan Karnan; Baiq Sri Handayani (Postgraduate, University of Mataram, 2022)
Coastal waters well known to provided large number of natural resources, but it recives some negative effects due to numerous ectivities take place on it, so it’s quality status tend to decrease. The coastal waters of Mandalika SEZ Central Lombok is no in exception. Microalgae as maind primery producent, have been much reported as bioindicator for controlling the waters quality. Study for community of microalgae as bioindicator in the coastal waters of Mandalika SEZ Central Lombok never been done. This study was conducted to observed and analyze the potency of microalgae community in the coastal waters of the Mandalika SEZ for determining the quality status that waters. Five bottles of 150 ml volume sea waters samples were collected using a free fall nylon plankton net of 20 πm mesh sized. Samples were preserved using formalin in final consentration of 4%. Samples were observed in both laboratories of Biology Education Faculty of Teacher Training and Education and Biology Science Faculty of Math and Science, University of Mataram. Data were analyzed for counting of density, percentage dominancy, and species diversity indexs. Total 72 species of microalgae were fully indentified and Chaetoceros didymum was a dominant species with percentage dominacy and density of 16.243% and 143.949 ind/L, respectively. The highest dencity was recorded in sample taken in the Seger Beach (1567.941 ind./L), then followed by the beaches of Gerupuk, Serinting, Mandalika, dan Kuta with density velue of 1469.214 ind./L, 1038.217 ind./L, 759.023 ind./L, and 622.081 ind./L, respectively. Based on the data of microalgae density, species diversity indexs, and number of taxa, the five sampling sites have high percentage similarity (83.336%). Species diversity index of microalgae in the coastal waters of the Mandalika SEZ was in intermediate category (H’=3.415). Based on the rerults of this study, mainly based on the velue of microalgae species diversity indexs, it can be concluded, that the quality status of coastal waters of Mandalika SEZ Central Lombok was in non polluted category